STRATEGI GURU DALAM MENGEMBANGKAN KETERAMPILAN KEWARGANEGARAAN (CIVIC SKILLS) SISWA - Pratama, Erviana Diah; Patmisari, Patmisari; Muthali’in, Achmad (Academy of Education Journal, 2023)
The purposes of this research is to find out the teacher’s strategy in developing the civic skills of students at SMA Negeri 1 Badegan. This research was carried out for approximately 5 month using a qualitative research method that is descriptive in nature by prioritizing facts in the field in order to provide a clear picture. The data and data sources for this study came from interviews with PPKn teachers and observations at school. This study uses observation instruments and interview instruments. Data collection techiques used in this research are observation, interview, and documentation techniques. The result of the study show that in developing citizenship skills a teacher must have the right strategy. There are several strategies carried out by teacher at SMA Negeri 1 Badegan to develop students’ civic skills. The first strategy is to carry out learning in groups and show the result of group discussions to increase student activity. The the second strategy is to create a pleasant classroom atmosphere. The third strategy is to implement cooperative learning. then, the last strategy is to feel the handshake culture when meeting when finishing learning and shaking hands when meeting with the teacher.